Impact of Social Media on Interpersonal Communication between Student and a Teacher - Taha Shabbir (Journal of Public Administration and Government, 2021)
The main aim of this research is to study how our interpersonal relationships are affected by social media. The main objective of this research is to find out whether there is an effect of social media on our education. The type of research we have chosen is a descriptive and mixed method of research. Our variables are family, friends, fellow colleagues, and fitness (mental/physical). The sample size we chose was 100, using convenience sampling and questionnaires. We used SPSS to analyze our data, hypotheses testing method. In our findings, we find out that 60% of our respondents used social media for 3-5hrs and 46% of our respondents disagreed that social media has worsened their personal relationships which means that social media has a much more positive effect on relationships than is popularly believed.